2021
DOI: 10.1088/1755-1315/668/1/012079
|View full text |Cite
|
Sign up to set email alerts
|

A Vector Ionospheric Delay Correction Method for GNSS Positioning and Navigation Wide Area Augmentation Service

Abstract: A new ionospheric delay correction method is proposed to improve the ionospheric correction accuracy of single frequency GNSS users. In the new method, the ionospheric grid point information is expanded from a single scalar vertical correction parameter to a vector of triple elements (the triple): vertical correction parameter, north correction parameter and east correction parameter. The new parameters are used to describe the variation of ionospheric delay correction caused by satellite azimuth. Using the ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…According to the requirements of being real-time, the frequency of serial port transmission data is 1 Hz, so the DSP processor should decode and filter the transmitted data within one second and the number of particles should not be too much. After repeated tests, it is found that the number of particles is 60 [9][10].…”
Section: System Design Of Gps Navigationmentioning
confidence: 99%
“…According to the requirements of being real-time, the frequency of serial port transmission data is 1 Hz, so the DSP processor should decode and filter the transmitted data within one second and the number of particles should not be too much. After repeated tests, it is found that the number of particles is 60 [9][10].…”
Section: System Design Of Gps Navigationmentioning
confidence: 99%